If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3k = 2k + -16 Reorder the terms: 3k = -16 + 2k Solving 3k = -16 + 2k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-2k' to each side of the equation. 3k + -2k = -16 + 2k + -2k Combine like terms: 3k + -2k = 1k 1k = -16 + 2k + -2k Combine like terms: 2k + -2k = 0 1k = -16 + 0 1k = -16 Divide each side by '1'. k = -16 Simplifying k = -16
| f(x)=(2x-1)(x+2)(x+3) | | (7x-1)(x-7)=0 | | -4(w-7)=-7w+19 | | 18=3(j-13) | | 2(4+7x)=-3(1-4x)+5 | | 2u+38=7(u-1) | | r-10/3=3 | | .42/7.00=x/100 | | (2x-1)(2x+7)=0 | | 3(p-13)+4=13 | | x^5-ax^2-ax+1=0 | | -6(8v-4)=6(6v+4) | | n+9=4v-6 | | 8y=3x-12 | | 2(1+8x)=4(4x+8) | | ax+y=bx+K | | -6(4x-6)=-18-6x | | (3i+8)(6i-7)= | | 4(x+5)-2x+2=3(2x-4)+x+9 | | x+90+70=180 | | -3(4v+8)=-18-6v | | H(t)=-16t^2+342+1000 | | 4/2x-2916=1/9 | | x^2+6x+12=2x-1 | | 30=-w+247 | | -7b+28=-8(5+3b) | | 4(32-2b)=144 | | 242-u=133 | | 1+7x=4x+16 | | 3(2x+5)=(3x+3) | | 5m+m-2m=20 | | 12n=7 |